Peningkatan Motorik Halus dengan Memanfaatkan Origami untuk Siswa Taman Kanak-kanak - Masrifah Masrifah; Dewi Sekar Arum; Ardica Karunia Pradana; Mila Hariani; Rahayu Mardikaningsih; Didit Darmawan; Mirza Elmy Safira (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
The golden age of children, which is often called the Golden Age, is when children are between 0 and 6 years old. At this stage of development, children grow and change rapidly. The aim of this community service is to improve students' fine motor skills through origami paper folding activities, including eye and hand coordination abilities, finger flexibility, and accuracy in carrying out fine movements. This project uses the ABCD (Asset Based Communities Development) strategy or method, which is a community development approach that emphasizes the assets and qualities that the community already has. In general, the results of the activity of improving fine motor skills by using origami for kindergarten students at Dharma Wanita Association 3 Tambak Lekok, namely the target of solving the problem in using origami paper to make carrots, are children who have never previously known and make ornamental plants from the material. origami paper, but in the activity of Improving Fine Motor Skills Using Origami for Kindergarten Students of Dharma Wanita Association 3 Tambak Lekok with enthusiasm to follow and learn together in making carrots from origami materials. Because with this creative activity, children of their age become increasingly curious about what they didn't know before, thus encouraging and encouraging them to learn together in paper folding activities.